Scotland's internal medicine simulation strategy: A 5-year journey - Joanne Kerins; Suzanne Anderson-Stirling; Jemma Pringle; Victoria Ruth Tallentire (Future Healthcare Journal)
In 2019, the internal medicine (IM) stage 1 curriculum was implemented in the UK. This introduced a revised 3-year training programme for physicians in training. The new IM stage 1 curriculum emphasised simulation-based education, triggering the integration of simulation training on a national scale in Scotland. Bespoke training courses were developed for IM trainees in Scotland, spanning all 3 years of their training programme. Each course was meticulously designed with input from key stakeholders and trainees, aligning learning objectives with curriculum outcomes. The Scottish IM simulation strategy encompasses a 3-day bootcamp in IM year 1, a 1-day skills day in IM year 2, and a 2-day ‘registrar ready’ course in IM year 3. These courses, delivered at central locations, focus on immersive simulation, communication workshops, and simulation-based mastery learning of procedural skills. Evaluation of the programme includes pre- and post-course questionnaires, data tracking over the training programme, interviews with trainees and faculty, and annual review days to gather feedback and make necessary adaptations. The impact of the programme for trainees includes transfer to clinical practice of communication skills, improved non-technical skills, and increased confidence in procedural skills. Alignment with the IM stage 1 curriculum supports trainees’ annual reviews of competence progression. The IM simulation training also offers valuable social benefits and remains crucial, especially with increased pressure in the NHS. It is our belief that ongoing delivery of this training is invaluable to the IM stage 1 programme in Scotland.